2021
DOI: 10.1001/jamanetworkopen.2020.34750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ruxolitinib for Steroid-Refractory Chronic Graft-vs-Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Key Points Question Is ruxolitinib an option for patients with steroid-refractory chronic graft-vs-host disease, and what characteristics are associated with treatment response? Findings In this case series of 41 patients with steroid-refractory chronic graft-vs-host disease who were treated with ruxolitinib, heavily pretreated patients could achieve meaningful responses with a favorable safety profile. No lung involvement and haploidentical donors were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Furthermore, recipients of MHC II KO BM supplemented with WT T cells (supplemental Figure 8E-F) demonstrated improved behavior in the FST at day 35 (supplemental Figure 8G) compared with recipients of WT BM plus T cells. Notably, MHC II deficiency did not diminish brain Ifng messenger RNA levels (supplemental Figure 8H), indicating that IFN-γ signaling functions upstream of and may be required for 55 MHC II expression by donor BMDMs to promote CNS cGVHD behavioral perturbations.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, recipients of MHC II KO BM supplemented with WT T cells (supplemental Figure 8E-F) demonstrated improved behavior in the FST at day 35 (supplemental Figure 8G) compared with recipients of WT BM plus T cells. Notably, MHC II deficiency did not diminish brain Ifng messenger RNA levels (supplemental Figure 8H), indicating that IFN-γ signaling functions upstream of and may be required for 55 MHC II expression by donor BMDMs to promote CNS cGVHD behavioral perturbations.…”
Section: Resultsmentioning
confidence: 97%
“…Other studies have reported similar relapse rates. 23 , 25 , 32 Choi et al and Carniti et al demonstrated that ruxolitinib treatment reduced GVHD and preserved the beneficial of GVT effect in murine models. 8 , 9 More prospective clinical trials are needed to determine whether ruxolitinib reduces the risk of relapse in patients compared with other immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early azithromycin administration in patients undergoing allogeneic HSCT is associated with worse airflow decline–free survival [ 48 ]. A recent case series found that ruxolitinib in patients with steroid refractory cGVHD had an overall response rate of 70.7%; however, the response is less favorable in patients with lung involvement [ 52 ]. A randomized clinical trial of ruxolitinib in treatment of cGVHD is currently underway (NCT03112603).…”
Section: Late Post-transplantation Period (>100 Days Post-transplant)mentioning
confidence: 99%